Modeling of electroplated diamond wire and its application towards precision slicing of semiconductors. (3rd February 2023) - Ge, Mengran; Zhang, Chenzheng; Wang, Peizhi; Li, Zongqiang; Ge, Peiqi
Abstract: Electroplated diamond multi-wire sawing is becoming the mainstream technique for semiconductor slicing, because of its desirable traits such as thin slice thickness, low kerf loss, and high surface/subsurface quality. Precisely describing the electroplated diamond wire is of significant importance to slicing process analysis. This study presents an electroplated diamond wire model based on statistical measurements of the cutting-edge geometry and scratching direction of abrasives on wire. These measurements are performed on a commercial wire (Diamond Wire-160) after exposing cutting edges from plated nickel layers. Results show that up to 91 % of abrasives have a single cutting edge with the shape of a triangular or quadrangular pyramid. The geometric angles ( α 1, α 2, γ 1, γ 2 ) of these pyramids are observed to follow an approximate Gaussian distribution, and the scratching direction follows a uniform distribution. Combined with nanoindentation theory, the developed model is further employed for slicing process analysis, in which slicing forces and bow angles of wire are calculated. Additionally, slicing experiments are conducted on silicon for model verification, and the maximum relative error between predicted and experimental bow angles is 6.25 %. The developed wire model provides an effective tool for slicing process analysis, thereby accelerating the process development for scale-up production of high-precision semiconductor substrates. Graphical abstract: Unlabelled Image Highlights: Electroplated diamond wire model is established based on statistical measurements. The model is applied to slicing process analysis combining nanoindentation theory. Slicing forces and bow angle of wire are calculated using the model. The model is verified by slicing experiments on silicon.